3p2 − 76 = –49

Write your answers as integers or as proper or improper fractions in simplest form.

p =

1 answer

To solve for p, we can start by isolating p on one side of the equation.

Adding 76 to both sides of the equation, we get:

3p2 = -49 + 76

3p2 = 27

Next, we divide both sides of the equation by 3:

p2 = 27/3

p2 = 9

Taking the square root of both sides, we get:

p = ±√9

Simplifying the square root, we have:

p = ±3

Therefore, the value of p is 3 or -3.
Similar Questions
  1. –2|d| = –4Write your answers as integers or as proper or improper fractions in simplest form.
    1. answers icon 23 answers
  2. Solve for y.-10= -5 |y| Write your answers as integers or as proper or improper fractions in simplest form. y = or y =
    1. answers icon 1 answer
  3. Solve for p.0 =|-4p| Write your answers as integers or as proper or improper fractions in simplest form. p = or p =
    1. answers icon 1 answer
  4. Solve for t.t^2 − 81 = –45 Write your answers as integers or as proper or improper fractions in simplest form. t = or t =
    1. answers icon 1 answer
more similar questions